1996
DOI: 10.1042/bj3180701
|View full text |Cite
|
Sign up to set email alerts
|

Release of secretory phospholipase A2 from rat neuronal cells and its possible function in the regulation of catecholamine secretion

Abstract: Here we show that secretory phospholipase A2 (sPLA2) that is immunochemically indistinguishable from type II sPLA2 is (i) stored in neuroendocrine cells, (ii) released in response to neurotransmitters or depolarization, and (iii) involved in the regulation of catecholamine secretion by these cells. Rat brain synaptic vesicle fractions contained PLA2 activity, which was neutralized completely by an antibody raised against rat type II sPLA2. sPLA2 immunoreactive with anti-(type II sPLA2) antibody was released fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 53 publications
(59 reference statements)
3
79
0
Order By: Relevance
“…Although both cPLA 2 and sPLA 2 were activated in some of those studies (Kim et al, 1995), it is likely that mainly cPLA 2 was activated in ours, as cPLA 2 is sensitive to the low Ca 2 + concentrations, 300 nM to 1 mM (Clark et al, 1995;Ismailov et al, 2004) that occur during normal neuronal activation. sPLA 2 activation requires a much higher Ca 2 + concentration, 16-18 mM, and is involved mainly in the presynaptic release of synaptic vesicles (Dennis, 1994;Matsuzawa et al, 1996;Wei et al, 2003). iPLA 2 is Ca 2 + -independent and selective for DHA acid rather than AA (Dennis, 1994;Strokin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both cPLA 2 and sPLA 2 were activated in some of those studies (Kim et al, 1995), it is likely that mainly cPLA 2 was activated in ours, as cPLA 2 is sensitive to the low Ca 2 + concentrations, 300 nM to 1 mM (Clark et al, 1995;Ismailov et al, 2004) that occur during normal neuronal activation. sPLA 2 activation requires a much higher Ca 2 + concentration, 16-18 mM, and is involved mainly in the presynaptic release of synaptic vesicles (Dennis, 1994;Matsuzawa et al, 1996;Wei et al, 2003). iPLA 2 is Ca 2 + -independent and selective for DHA acid rather than AA (Dennis, 1994;Strokin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…cPLA 2 has been localized at postsynaptic neuronal membranes in the brain (Basavarajappa et al, 1998;Ong et al, 1999;Pardue et al, 2003) and is activated by 300 nM to 1 mM Ca 2 + (Clark et al, 1995), in the physiological range of intracellular Ca 2 + during neuronal activation (Ismailov et al, 2004). sPLA 2 is activated at much higher Ca 2 + concentrations, 16-18 mM (Dennis, 1994), and is localized in presynaptic vesicles that are released by exocytosis during membrane depolarization (Matsuzawa et al, 1996;Wei et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For neural differentiation, the cells (10 4 cells/ml) were cultured with appropriate concentrations of rat nerve growth factor (NGF; Sigma) in type I collagen-coated 6-or 12-well plates (Iwaki Glass) for up to 3 days (14). Normal human pulmonary fibroblasts (NHPF) and culture media with supplements for these cells were purchased from BioWhittaker.…”
Section: Methodsmentioning
confidence: 99%
“…2D), indicating that sPLA 2 -X accumulates in the Golgi prior to secretion. sPLA 2 -X Induces Neurite Outgrowth in PC12 Cells-In an attempt to identify some functional aspects of sPLA 2 -X in peripheral neuronal cells, we took advantage of PC12 cells, which differentiate into sympathetic neuron-like cells following culture with 100 ng/ml NGF (14), as shown in Fig. 3A.…”
Section: Spla 2 -X Is Expressed In Peripheral Neuronal Fibers In Var-mentioning
confidence: 99%
“…Several phospholipases A2 have been identified that preferentially hydrolyze phosphatidic acid. These include a phospholipase A2 activity enriched in the brain and a secretory phospholipase A2, which is synthesized in astrocytes in response to inflammatory mediators, elevated in activity on cerebral ischemia/reperfusion, and released in conjunction with neurotransmitter release from synaptic vesicles (Oka and Arita, 1991;Lauritzen et a!., 1994;Fourcade et a!., 1995;Thomson and Clark, 1995;Matsuzawa et al, 1996;Snitko eta!., 1997). It is interesting that a related secretory phospho!ipase A2, was found to synergize with glutamate in the stimulation of neuronal death (Kolko et a!., 1996).…”
Section: Lpa Induces a Decrease In Mitochondrial Membrane Potentialmentioning
confidence: 99%